Managing sustainability of energy transition among expert engineers: Co-creating technopreneurial orientation - Yud Buana; Tirta Nugraha Mursitama; Sri Bramantoro Abdinagoro; Yosef Dedy Pradipto (Global Business & Finance Review (GBFR), 2022)
Purpose: Research to improve co-creation in engineering and technopreneurial orientation is required to support the energy transition toward sustainability. This challenge is aimed at power system expert engineers, whose central role in the electricity sector is becoming increasingly complicated by the possibility of stranded assets, intermittency paradigms, and new patterns of energy flow. This research explains the importance of the co-creation process as a mediator to enable the utilization of the technopreneurial orientation among expert engineers in supporting the sustainability of the electricity sector. Design/methodology/approach: The survey method was carried out to collect data from expert power system engineers with more than ten years of experience in the national electricity sector. The quantitative method with structural equation modeling analysis and a partial least square approach was used in this research. Findings: Empowering expert engineers in a technopreneurial orientation can encourage them to co-create by prioritizing dialogue that allows for accessibility and transparency when taking risks, which is an important aspect that boosts the co-creation effect in the energy transition to sustainability. The strong behavior of experts in utilizing technopreneurial orientation and the co-creation process has been demonstrated to be capability of adopting the three aspects contained in the energy trilemma index, energy security, energy equity, and environmental sustainability, which are modified to reflect a strong tendency to achieve sustainability in the electricity sector. Research limitations/implications: Although this study's respondents are limited to expert engineers in the electricity sector, the findings have implications for the management of experts in other strategic and large-scale sectors. The limited number of respondents to expert engineers with more than ten years of work experience makes millennials excluded. Originality/value: The measurement indicator becomes novelty in this study. Sustainability was adopted and modified from the energy trilemma index. Technopreneurial orientation adopted from Lumpkin & Dess (1996) was modified by the addition of technological expertise. Then, co-creation as a mediator is taken from the DART of value co-creation.
Keywords: 650; Sustainability; Co-creation; Technopreneurial Orientation; Energy Transition; Expert Engineer